Meta-Analysis of Reciprocal Linkages between Temperate Seagrasses and Waterfowl with Implications for Conservation - Kollars, Nicole M.; Henry, Amy K.; Whalen, Matthew A.; Boyer, Katharyn E.; Cusson, Mathieu; Eklöf, Johan S.; Hereu, Clara M.; Jorgensen, Pablo; Kiriakopolos, Stephanie L.; Reynolds, Pamela L.; Tomas, Fiona; Turner, Mo S.; et al. (Frontiers in Plant Science, 2017)
Multi-trophic conservation and management strategies may be necessary if reciprocal linkages between primary producers and their consumers are strong. While herbivory on aquatic plants is well-studied, direct top-down control of seagrass populations has received comparatively little attention, particularly in temperate regions. Herein, we used qualitative and meta-analytic approaches to assess the scope and consequences of avian (primarily waterfowl) herbivory on temperate seagrasses of the genus Zostera. Meta-analyses revealed widespread evidence of spatio-temporal correlations between Zostera and waterfowl abundances as well as strong top-down effects of grazing on Zostera. We also documented the identity and diversity of avian species reported to consume Zostera and qualitatively assessed their potential to exert top-down control. Our results demonstrate that Zostera and their avian herbivores are ecologically linked and we suggest that bird herbivory may influence the spatial structure, composition, and functioning of the seagrass ecosystem. Therefore, the consequences of avian herbivory should be considered in the management of seagrass populations. Of particular concern are instances of seagrass overgrazing by waterfowl which result in long-term reductions in seagrass biomass or coverage, with subsequent impacts on local populations of waterfowl and other seagrass-affiliated species. While our results showed that bird density and type may affect the magnitude of the top-down effects of avian herbivory, empirical research on the strength, context-dependency, and indirect effects of waterfowl-Zostera interactions remains limited. For example, increased efforts that explicitly measure the effects of different functional groups of birds on seagrass abundance and/or document how climate change-driven shifts in waterfowl migratory patterns impact seagrass phenology and population structure will advance research programs for both ecologists and managers concerned with the joint conservation of both seagrasses and their avian herbivores.